The Effect of Family Support on Functional Recovery of Post-Stroke Patients at Haji General Hospital Medan in 2026 - Ira Maulani Lubis; Julaiha Siregar (Journal of Innovative and Creativity, 2026)
Background: Stroke remains a leading cause of long-term disability worldwide, significantly impairing patients' functional independence. Family support has been recognized as a critical psychosocial factor that may influence rehabilitation outcomes; however, empirical evidence from Indonesian hospital settings, particularly in North Sumatra, remains limited. The purpose of this study was to analyze the effect of family support on the functional recovery of post-stroke patients at Haji General Hospital Medan in 2026. Methods: A descriptive correlational cross-sectional design was employed. Participants were 87 post-stroke patients recruited through purposive sampling between September and December 2025. Inclusion criteria required patients to have been diagnosed with stroke at least one month prior, be aged 18 years or older, and have a primary family caregiver. Data on family support were collected using the adapted Hensarling Diabetes Family Support Scale (HDFSS), and functional recovery was assessed using the Barthel Index (BI). Ethical clearance was obtained from the institutional review board. Data were analyzed using SPSS version 26, with Spearman's rank correlation coefficient applied to test the hypotheses (alpha = 0.05). Results: Of 87 participants, 52.9% reported high family support and 55.2% demonstrated good functional recovery (Barthel Index score ≥ 61). Spearman's rank correlation analysis revealed a statistically significant moderate positive relationship between overall family support and functional recovery (r = 0.541; p = 0.001). All four sub-dimensions of family support (informational, emotional, instrumental, and appraisal) were significantly correlated with functional recovery (p < 0.05). Conclusion: Family support exerts a significant positive effect on the functional recovery of post-stroke patients. Healthcare providers and hospital management should develop structured family-centered care programs to optimize rehabilitation outcomes for post-stroke patients